GP-support by means of AGnES-practice assistants and the use of telecare devices in a sparsely populated region in Northern Germany – proof of concept - Scriba Sibylle; Heymann Romy; Meinke Claudia; Fiß Thomas; Berg Neeltje; Hoffmann Wolfgang (BMC Family Practice, 2009)
Abstract Background In many rural regions in Germany, the proportion of the elderly population increases rapidly. Simultaneously, about one-third of the presently active GPs will retire until 2010. Often it is difficult to find successors for vacant GP-practices. These regions require innovative concepts to avoid the imminent shortage in primary health care. The AGnES-concept comprises the delegation of GP-home visits to qualified AGnES-practice assistants (AGnES: GP-supporting, community-based, e-health-assisted, systemic intervention). Main objectives were the assessment of the acceptance of the AGnES-concept by the participating GPs, patients, and AGnES-practice assistants, the kind of delegated tasks, and the feasibility of home telecare in a GP-practice. Methods In this paper, we report first results of the implementation of this concept in regular GP-practices, conducted November 2005 – March 2007 on the Island of Rügen, Mecklenburg-Western Pomerania, Germany. This study was meant as a proof of concept. The GP delegated routine home-visits to qualified practice employees (here: registered nurses). Eligible patients were provided with telecare-devices to monitor disease-related physiological values. All delegated tasks, modules conducted and questionnaire responses were documented. The participating patients were asked for their acceptance based on standardized questionnaires. The GPs and AGnES-practice assistants were asked for their judgement about different project components, the quality of health care provision and the competences of the AGnES-practice assistants. Results 550 home visits were conducted. 105 patients, two GPs and three AGnES-practice assistants (all registered nurses) participated in the project. 48 patients used telecare-devices to monitor health parameters. 87.4% of the patients accepted AGnES-care as comparable to common GP-care. In the course of the project, the GPs delegated an increasing number of both monitoring and interventional tasks to the AGnES-practice assistants. The GPs agreed that delegating tasks to a qualified practice assistant relieves them in their daily work. Conclusion A part of the GPs home visits can be delegated to AGnES-practice assistants to support GPs in regions with an imminent or already existing undersupply in primary care. The project triggered discussions among the institutions involved in the German healthcare system and supported a reconciliation of the respective competences of physicians and other medical professions.